Applicability of the drainage effectiveness of Blake drains and Tenckhoff catheters in the peritoneal dialysis of healthy rabbits (Oryctolagus cuniculus) - Pereira, Ana Camila [UNESP]; Geraldes, Silvano S. [UNESP]; Maia, Suellen R. [UNESP]; de Azevedo, Maria Gabriela P. [UNESP]; da Silva, Gustavo G. [UNESP]; de Souza, Bruna N. [UNESP]; García, Henry David M. [UNESP]; Melchert, Alessandra [UNESP]; Brandão, Cláudia Valéria S. [UNESP]; de Souza, Fabiana F. [UNESP]; Guimarães-Okamoto, Priscylla T. C. [UNESP] (Wiley, 2022)
Objective: To compare the efficacy of dialysate drainage between Tenckhoff (TC) catheter and Blake (BL) in peritoneal dialysis (PD) in healthy rabbits. Design: Prospective experimental study. Setting: University Teaching Hospital and University research laboratory. Animals: Twenty healthy, male, New Zealand rabbits. Interventions: PD via the TC catheter and the BL abdominal drain was compared during 3 consecutive days of dialysis delivery. Measurements and Main Results: One session of PD was performed per day for 3 consecutive days (S1: first session, S2: second session, S3: third session) and each session included 4 cycles of infusion, dwell of dialysate in the abdomen, and drainage. Data collection included daily urea, creatinine, alanine aminotransferase, albumin, and potassium, in addition to hematological parameters (eg, RBC, HCT, hemoglobin, WBC, and platelet count). Statistical analysis using a mixed linear model with multiple comparisons was performed. The BL drain resulted in an increase in volume drained (ml/kg) when compared to TC catheter on S2 (third and fourth cycles) and S3 (first and second cycles). Conclusions: The BL drain proved to be superior to the TC catheter, being capable of draining a larger volume of dialysate during the drainage processes in the peritoneal PD of healthy rabbits. The TC catheter had major complications with regard to fluid retention in the abdomen, representing reduced drainage efficiency, while the BL drain showed a greater tendency for the peritoneal fluid to leak.
Keywords: dialysis treatment; kidney injury; peritoneum; uremic toxins